Baffling telemetry detections can be useful: an acoustic receiver design to monitor organisms along reserve boundaries and ecotones. Issue 1 (December 2016) - Kendall, Matthew; Monaco, Mark; Winship, Arliss
Abstract Background Many biotelemetry studies seek to detect movement of organisms across reserve boundaries or between adjacent habitat areas. Our objective was to enhance this capability in studies of aquatic organisms that are tagged with acoustic transmitters and tracked by passive data loggers. We installed an experimental shroud on a commercially available telemetry receiver. The shroud was designed to baffle incoming signals from transmitters along one hemisphere of the receiver and therefore more conclusively determine which side of a boundary line that a tagged organism occupies. Results Range testing of shroud effectiveness was conducted along the border of a marine-protected area in a coral reef ecosystem. A transmitter of the type implanted into reef fish was deployed in various directions, distances, and landscape settings relative to 11 shrouded receivers. There was a significant difference in the detectability of transmissions on the shrouded versus unshrouded side of the receivers. On the unshrouded hemisphere of the receiver, 75–100 % of transmissions within 100 m were detected and maximum effective detection range was ~180 m. On the shrouded hemisphere of the receiver, detections were rare at any distance with a maximum of 12 % of transmissions recorded even as close as 60 m away. Conclusions The shroud modified the detection area of a standard omni-directional receiver into a hemi-directional receiver better able to detect transboundary presence. The approach is useful for applications that require detection of simple boundary-crossing events using a minimal number of receivers.